Impact of tumor histology on detection of pelvic and para-aortic nodal metastasis with FDG-PET in stage IB cervical cancer - Lin, Alexander J. (Int J Gynecol Cancer, 2019)
OBJECTIVE: FDG-PET detection of metastatic nodal disease is useful for guiding cervical cancer treatment, but the impact of tumor histology is unknown. This study reports the detection of FDG-avid pelvic and para-aortic lymph nodes in early stage cervical cancer patients with squamous carcinoma and adenocarcinoma tumor histology. METHODS: Patients with FIGO 2009 stage IB1–2 cervical cancer who underwent pre-surgical FDG-PET between March 1999-February 2018 were identified in a tertiary academic center database. All patients had radical hysterectomy with pelvic and para-aortic lymph node dissection. The detection of pelvic and para-aortic lymph nodes by FDG-PET vs. surgical dissection was compared. FDG-PET sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) were determined and stratified by tumor histology. RESULTS: We identified 212 patients with early-stage cervical cancer (84% FIGO IB1, 16% IB2) who underwent pre-surgical FDG-PET; 137(65%) patients had squamous carcinoma and 75 (35%) patients had adenocarcinoma. PET/CT was performed in 189 (89%) patients and 23 (11%) had PET only. Surgical dissection revealed positive pelvic and para-aortic lymph nodes in 25% and 3.3% of patients, respectively. For squamous carcinoma, the sensitivity, specificity, PPV and NPV of FDG-PET for pelvic nodal metastasis were 44%, 99%, 95% and 78%; respectively. For adenocarcinoma, the corresponding results for pelvic nodal metastasis were 25%, 99%, 67% and 92%; respectively. The overall sensitivity, specificity, PPV and NPV of FDG-PET for para-aortic nodal metastasis was 29%, 99%, 67%, and 98%; respectively. DISCUSSION: Pelvic nodal metastasis was less likely to be detected by FDG-PET in patients with early-stage adenocarcinoma than with squamous carcinoma.